ESTIMATION OF OVERPRESSURE BASED ON WIRELINE LOGS IN SUB-BASIN OF LEMATANG, SOUTH SUMATRA - M Nurdin, Didin
The Lematang Sub-Basin is a sub-basin located in the northern part of South Sumatra Basin. This area is chosen to be the study area because it has indications of the presence of overpressure in form of thick layer of shale (500-13000 feet) and high thermal gradient (2,710 F/100 feet). The purpose of this research is to determine the characteristic of overpressure and to estimate overpressure by using the Eaton method and to determine the distribution of the overpressure zones in the study area. The data used in this study are drilling data (direct measurement of pore pressure and the final drilling report), wireline log data (log gamma ray, resistivity, density, neutron, and sonic), and supporting data (description of rock and geochemical data). In the study area, the top overpressure is located within Air Benakat Formation with unloading as the generating mechanism due to transformation of clay mineral, i.e smectite to illite transformation as observed in AP-1 and AP-2 wells. In the research area, top of overpressure deepens to the basin center. Further, Eaton’s method with the exponent of 3 is sufficient to estimate overpressure in the study area.